Study and Assessment of the Microclimate of Hospital Rooms (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Studying and assessing the microclimate of hospital rooms is a crucial aspect of ensuring patient comfort and well-being. The microclimate refers to the immediate environment within a room, including factors such as temperature, humidity, air quality, and noise levels. Maintaining optimal conditions in hospital rooms is essential for patient recovery and preventing the spread of infections. In this article, we will explore the importance of studying the microclimate in hospital rooms and discuss key factors that contribute to a healthy and comfortable environment.